Analyzing the Link and Match Gap: A Comprehensive Review of Vocational Training Outcomes in Indonesia - Lutfi Ariefianto; Rody Putra Sartika; Natalino Parada (Journal of Nonformal Education, 2026)
Background - Indonesia is the world’s largest archipelagic country with a population of approximately 281.8 million in 2023, representing both enormous labor potential and significant workforce management challenges. This study is grounded in Law No. 20 of 2003 on the National Education System, which mandates the development of students’ potential, skills, and character. The transition toward the Industrial Revolution 4.0 and Society 5.0 has significantly transformed workforce competency requirements, demanding higher levels of adaptability, technological literacy, and professional skills. In response, the Indonesian government has expanded the establishment of Vocational Training Centers (Balai Latihan Kerja / BLK) across the country. However, the expansion in quantity has not been fully accompanied by improvements in training quality and labor market relevance. Research Urgency -  Several challenges highlight the urgency of this research: 1) persistent unemployment – Despite the increasing number of vocational training institutions, the Open Unemployment Rate (TPT) remains relatively high, indicating limited effectiveness in labor market absorption; 2) skill discrepancy – There is a significant mismatch between the competencies produced by vocational education and training institutions and the actual skill requirements of industry partners; 3) competitive pressure – Without improving workforce competencies, domestic labor risks being replaced by more competitive foreign workers in an increasingly globalized labor market; 4) need for synthesis – There is a critical need to systematically identify the root causes of the link-and-match gap to provide evidence-based policy recommendations. Research Objectives - The analysis identified ten major factors contributing to the gap, including curriculum misalignment, outdated infrastructure, weak industry collaboration, and insufficient integration of soft skills and technical competencies. Furthermore, the link-and-match gap can be categorized into four main dimensions: quality (competency levels), quantity (labor supply and demand imbalance), location (geographical distribution of skills), and timing (graduate readiness in relation to labor market needs). Research Method - This study employs a qualitative approach using the Systematic Literature Review (SLR) method. The SLR approach involves identifying, evaluating, and synthesizing relevant studies related to vocational education and training outcomes in Indonesia in order to understand the causes of the link-and-match gap. Research Findings - The analysis identified 10 primary factors contributing to the gap, including curriculum rigidity, outdated infrastructure, and a lack of integration between soft skills and hard skills. The gap is categorized into four dimensions: quality (competency levels), quantity (supply vs. demand), location (geographical distribution of skills), and timing (readiness of graduates when needed). Research Conclusion - Addressing the link-and-match gap requires the implementation of a pentahelix collaboration model involving government, academia, industry, society, and media. Vocational education institutions must shift from a supply-driven approach toward a demand-driven approach by actively involving industry stakeholders in curriculum development and implementing intensive work-based learning and apprenticeship program.